A synergistic embedded reinforcement method based on low-carbon geopolymer and small-diameter FRP bars
Patent Information
- Application Number
- CN202610876952.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-17
- Publication Date
- 2026-08-28
AI Technical Summary
本发明旨在提供一种低碳地聚物与小直径FRP筋协同内嵌加固方法,以解决现有FRP加固技术中新增外包层导致原构件截面和自重增加、现有工艺对小直径FRP筋与无机胶凝材料的适配性不足以及槽内施工工艺衔接不够明确的问题
[0012] Beneficial effects: Compared with the prior art, the present invention achieves the following beneficial effects through the synergistic effect of low-carbon geopolymer mortar, small-diameter FRP reinforcement and step-by-step construction process for the interface inside the trench.
Smart Images

Figure CN122649602A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of concrete structure repair and reinforcement technology, and in particular to a method for synergistic internal reinforcement of low-carbon geopolymer and small-diameter FRP bars. Background Technology
[0002] Concrete flexural members are widely used in buildings, bridges, ports and industrial plants. When the load-bearing capacity of a member decreases due to service environment, load increase or durability decline, it is usually necessary to use external bonding or embedded reinforcement technology to repair and strengthen it.
[0003] Existing technologies, such as the scheme for strengthening reinforced concrete beams using geopolymer-bonded mini CFRP bars disclosed in Peng Kaidi's 2022 doctoral dissertation, "Strengthening of reinforced concrete beam using geopolymer bonded mini CFRP bar," employ geopolymer mortar as an inorganic bonding matrix and combine small-diameter CFRP bars with the geopolymer mortar for reinforcing reinforced concrete beams. This approach can overcome, to some extent, the shortcomings of traditional epoxy resin-based bonding materials in terms of high-temperature resistance and durability. According to its reinforcement structure and construction method, this type of scheme mainly involves forming a new geopolymer mortar reinforcement layer on the tension side of the original concrete beam, and arranging the small-diameter CFRP bars within the new mortar layer, allowing the newly added reinforcement layer to share the load with the original component.
[0004] However, the reinforcement methods described above require the formation of a new reinforcement layer on the outside of the original component, which typically increases the component's cross-sectional dimensions and structural weight, and may affect the building's clearance or the component's appearance. Furthermore, their focus is on the combined reinforcement effect of the polymer mortar layer and small-diameter CFRP bars. The constraints on the process of cleaning the trench, wetting the trench walls, layered pouring, vibration compaction, and curing and finishing when locally slotting within the original concrete cover for near-surface embedding reinforcement are still insufficient. In addition, existing methods lack targeted material composition and construction control for the mortar's fluidity, wrapping density, and interfacial bonding stability after further reducing the FRP bar diameter. Therefore, it is still necessary to propose a method for the synergistic embedding reinforcement of low-carbon polymers and small-diameter FRP bars, implemented with minimal changes to the original component's cross-section and weight. Summary of the Invention
[0005] Technical issues This invention aims to provide a method for synergistic internal reinforcement of low-carbon geopolymers and small-diameter FRP bars, in order to solve the problems in existing FRP reinforcement technologies, such as the increase in the cross-section and self-weight of the original component due to the addition of an outer cladding layer, the insufficient compatibility of existing processes with small-diameter FRP bars and inorganic cementitious materials, and the unclear connection of construction processes in trenches.
[0006] The technical solution of the present invention to solve the above-mentioned technical problems is as follows: A synergistic embedding reinforcement method based on low-carbon geopolymers and small-diameter FRP bars is proposed, including the following steps: S1. Use a grooving machine to open a groove in the concrete cover at the bottom of the concrete bending member to be reinforced along the direction of force, and wash the concrete debris in the groove with running water. S2. Prepare the geopolymer mortar according to the following mass parts: 500-600 parts slag, 140-150 parts fly ash, 200-300 parts silica fume, 250-300 parts 800-mesh quartz sand, 350-400 parts 70-110-mesh quartz sand, 200-220 parts 40-70-mesh quartz sand, 150-160 parts 20-40-mesh quartz sand, 40-45 parts solid sodium hydroxide, 260-280 parts water, 330-350 parts water glass solution, and 15-25 parts polycarboxylate superplasticizer. First, mix the slag, fly ash, and silica fume evenly. Then, add the various grades of quartz sand and the polycarboxylate superplasticizer and dry mix for 1-2 minutes. Finally, add the pre-mixed 2... h The prepared alkali activator is wet-mixed for 3 minutes. The alkali activator is prepared by first slowly adding water to a water glass solution and stirring, and then adding solid sodium hydroxide until it is completely dissolved. S3. Prepare small-diameter FRP reinforcement bars with a diameter of 0.5-1.5 mm according to the required length of the structure to be reinforced, and clean the dust from the surface of the reinforcement bars; S4. Use alcohol-soaked cotton balls to clean the residue and dust in the tank. After the alcohol has completely evaporated, wet the inner wall of the tank with a wet cotton ball. First, pour the bottom layer of polymer mortar into the tank. Then, evenly arrange the small-diameter FRP reinforcement in the tank. Next, pour the top layer of polymer mortar and vibrate for 4-5 minutes to make the polymer mortar cover each small-diameter FRP reinforcement. Finally, smooth the surface of the polymer mortar. S5. After covering the surface of the reinforcement system with water-retaining cotton and curing it with water for 28 days, the reinforced surface is polished and repaired.
[0007] Furthermore, in step S1, the grooving speed is controlled at 20-30 cm / min, the grooving width is 10-20 mm, and the grooving depth is determined based on the thickness of the reinforcing steel protective layer of the reinforced concrete bending member.
[0008] Furthermore, the density of the small-diameter FRP reinforcement is 1.5 g / cm³. 3 The tensile strength is not less than 2000 MPa, the elastic modulus is not less than 210 GPa, and the elongation is not less than 1.8%.
[0009] Furthermore, in step S3, the small-diameter FRP reinforcing bar is subjected to surface sandblasting or grinding treatment.
[0010] Furthermore, the small-diameter FRP reinforcement is a small-diameter CFRP reinforcement.
[0011] Furthermore, the concrete bending member to be reinforced is a reinforced concrete beam, and the bottom of the reinforced concrete beam has at least two slots for arranging the small-diameter FRP reinforcement.
[0012] Beneficial effects: Compared with the prior art, the present invention achieves the following beneficial effects through the synergistic effect of low-carbon geopolymer mortar, small-diameter FRP reinforcement and step-by-step construction process for the interface inside the trench.
[0013] First, this invention combines localized slotting within the concrete protective layer, embedded small-diameter FRP reinforcement, and filling of the groove with low-carbon polymer mortar, thereby transferring the reinforcing material from the outer surface of the original component to the groove within the original component's protective layer. This avoids, on the one hand, the problems of increased cross-sectional dimensions, increased structural weight, and limited clearance caused by the increased cross-sectional area required by the cross-section-enlarging reinforcement route represented by D1, which necessitates the formation of a new solid layer on the tension side of the original component; on the other hand, the groove provides lateral constraint to the small-diameter FRP reinforcement and polymer mortar, enabling the reinforcement system to participate in flexural bearing with minimal alteration to the original component's shape.
[0014] Secondly, this invention combines 0.5-1.5 mm small-diameter FRP bars with geopolymer mortar containing multi-graded quartz sand, slag, fly ash, and silica fume. The small-diameter FRP bars provide a larger relative bonding contact area within the equivalent reinforced cross-sectional area, while the multi-graded geopolymer mortar enhances the filling and wrapping ability of the gaps around the bars during trench filling. Together, they improve the stress transfer conditions at the bar-mortar interface, thereby increasing the utilization rate of FRP materials and reducing the risk of interface delamination.
[0015] Third, this invention combines pre-preparation of the alkali activator, step-by-step mixing of dry materials, control of wet mixing time, and layered pouring within the tank. This ensures that the polymer mortar has a relatively stable mixing state before entering the tank, and first forms a bottom layer of mortar support within the tank, before arranging small-diameter FRP bars and pouring the upper layer of mortar. This coordinated preparation and pouring sequence reduces local gaps and uneven wrapping problems when arranging small-diameter FRP bars within the tank, improving the continuity and density of the polymer mortar's wrapping of multiple small-diameter FRP bars.
[0016] Fourth, this invention employs alcohol cleaning of the trench, wetting with damp cotton balls after alcohol evaporation, 4-5 minutes of vibration after layered pouring, and 28 days of water-retaining curing as continuous interface control processes. Alcohol cleaning removes residue and dust from the trench; wetting with damp cotton balls reduces the localized water absorption of the polymer mortar by the concrete trench walls; vibration promotes the mortar's penetration into the gaps between small-diameter FRP bars and between the bars and the trench walls; and water-retaining curing ensures the later-stage reaction and strength development of the polymer mortar. The continuous action of these processes creates a more stable interface bond between the trench walls, mortar, and small-diameter FRP bars, solving the problem of bond stability fluctuations caused by insufficient interface treatment and construction connections in existing technologies.
[0017] Fifth, the combined effects of the locally slotted embedded arrangement, the large relative contact area of the small-diameter FRP bars, the inorganic cementitious properties of the low-carbon geopolymer mortar, and the continuous interface construction control in this invention enable the reinforcement system to possess both high material utilization, strong anti-peeling ability, and good durability. Compared with solutions using organic resins or adding an external reinforcement layer, this invention can improve the long-term service stability of reinforced components while reducing carbon emissions and material costs, making it suitable for the reinforcement and repair of reinforced concrete flexural members in buildings, bridges, ports, and industrial plants. Attached Figure Description
[0018] Figure 1 This is a schematic cross-sectional view of the reinforced concrete beam strengthening component structure in an embodiment of the present invention.
[0019] Figure 2 This is a schematic diagram of the internal structure of the reinforced concrete beam strengthening component in an embodiment of the present invention. Detailed Implementation
[0020] To enable those skilled in the art to better understand the technical solution of the present invention, the present invention will be further described below in conjunction with the accompanying drawings and specific embodiments. It should be understood that the following embodiments are only for illustrating the present invention and are not intended to limit the scope of protection of the present invention.
[0021] like Figure 1 and Figure 2 As shown, the reinforcement object of this invention is preferably a reinforced concrete beam 1, the small-diameter FRP reinforcement is preferably a small-diameter CFRP bar 2, and the geopolymer bonding material is geopolymer mortar 3. At least two slots are provided at the bottom of the reinforced concrete beam 1 for arranging the small-diameter FRP reinforcement. The small-diameter CFRP bar 2 is embedded in the slots and fixed by the geopolymer mortar 3 to form a synergistic embedded reinforcement system. Unlike the method of increasing the cross-section by adding a new reinforcement layer to the outside of the original component, this embodiment mainly utilizes local slotting in the concrete protective layer to achieve embedded reinforcement, thereby completing bending reinforcement with minimal changes to the original component's shape and self-weight.
[0022] In practice, the first step is to groove the bottom of the concrete flexural member to be reinforced. The grooving operation is preferably performed using a grooving machine to directionally groove within the concrete cover along the direction of stress. The grooving speed should be controlled at 20–30 cm / min to reduce concrete chipping and ensure the groove does not shift. After grooving, concrete debris is flushed away from the groove with running water. The groove width can be 10–20 mm, and the groove depth is determined based on the thickness of the reinforcing steel cover in the reinforced concrete flexural member.
[0023] Subsequently, geopolymer mortar 3 is prepared. The geopolymer mortar 3 comprises, by weight, 500–600 parts slag, 140–150 parts fly ash, 200–300 parts silica fume, 250–300 parts 800-mesh quartz sand, 350–400 parts 70–110-mesh quartz sand, 200–220 parts 40–70-mesh quartz sand, 150–160 parts 20–40-mesh quartz sand, 40–45 parts solid sodium hydroxide, 260–280 parts water, 330–350 parts water glass solution, and 15–25 parts polycarboxylate superplasticizer. Preferably, water is first slowly added to a water glass solution while stirring, followed by the addition of solid sodium hydroxide until completely dissolved to prepare an alkali activator. The alkali activator is preferably prepared 2 hours in advance. Then, slag, fly ash, and silica fume are premixed evenly, followed by the addition of various grades of quartz sand and polycarboxylate superplasticizer, which are dry-mixed for 1–2 minutes. After the dry materials are evenly mixed, the alkali activator is added and wet-mixed for 3 minutes. The above components and processes, when combined, form a low-carbon geopolymer mortar system for casting in the trench and wrapping the small-diameter FRP reinforcement.
[0024] During the reinforcement preparation stage, small-diameter FRP reinforcement bars are prepared according to the required length of the structure to be reinforced, and the surface dust of the reinforcement bars is cleaned. The diameter of the small-diameter FRP reinforcement bars can be 0.5–1.5 mm. Preferably, the small-diameter FRP reinforcement bars are small-diameter CFRP bars 2, with a cross-sectional diameter of 1 mm and a density of 1.5 g / cm³. 3 The tensile strength is not less than 2000 MPa, the elastic modulus is not less than 210 GPa, and the elongation is not less than 1.8%. To further enhance the interfacial bonding ability, the small-diameter FRP reinforcement can also be surface sandblasted or ground before being arranged.
[0025] During the reinforcement pouring stage, use alcohol-soaked cotton balls to clean the residue and dust from the trench. After the alcohol has completely evaporated, moisten the inner wall of the trench with a damp cotton ball. Then, first pour the bottom layer of polymer mortar 3 into the trench, then evenly arrange the small-diameter CFRP bars 2 in the trench, and then pour the top layer of polymer mortar 3. During the pouring process, it is preferable to use a tool to vibrate for 4–5 minutes to ensure that the polymer mortar 3 fully coats each small-diameter CFRP bar 2. After pouring, smooth the surface of the polymer mortar 3.
[0026] During the curing and finishing stage, the surface of the reinforcement system is covered with water-retaining cotton and sprayed with water for 28 days. After the curing is completed, the reinforced surface is polished and finished to complete the method of co-embedded reinforcement of low-carbon geopolymer and small-diameter FRP bar.
[0027] As a specific embodiment, a reinforced concrete beam 1 with a cross-sectional dimension of 150 mm * 200 mm and a length of 1800 mm was selected for reinforcement. The reinforced concrete beam 1 uses C30 concrete with a reinforcement ratio of 0.59%. First, two grooves with dimensions of 15 mm * 15 mm and a length of 1300 mm were opened at the bottom of the reinforced concrete beam 1 at a speed of approximately 25 cm / min. Debris and residue in the grooves were removed, and the actual groove opening parameters were checked to control the groove opening error within 0.5 mm. Subsequently, an alkali activator was prepared 2 hours in advance, and geopolymer mortar 3 was prepared according to the above process flow. Then, 72 small-diameter CFRP bars 2 with a diameter of 1 mm were prepared, with 36 bars arranged in each groove; the small-diameter CFRP bars 2 underwent surface dust removal before arrangement and could be sandblasted or ground as needed. Before pouring, use an alcohol-soaked cotton ball to clean the residue and dust in the trench. After the alcohol has completely evaporated, moisten the inner wall of the trench with a wet cotton ball. After pouring the bottom layer of polymer mortar 3, evenly arrange the small-diameter CFRP bars 2 in the trench. Then pour the top layer of polymer mortar 3 and vibrate for 4–5 minutes until the polymer mortar 3 covers each small-diameter CFRP bar 2. After pouring, smooth out the bonding material.
[0028] The bottom surface of the reinforced concrete beam 1 was covered with absorbent cotton felt for curing, and water was added regularly to ensure full hydration of the polymer mortar 3. Curing was carried out for more than 28 days. After curing, the reinforced surface was ground and repaired. Four-point bending tests showed that the ultimate load of the reinforced concrete beam increased from 51.80 kN to 89.49 kN, an increase of 72.76%. This indicates that the low-carbon polymer and the small-diameter FRP reinforcement formed a good synergistic stress-bearing effect, which can improve the load-bearing capacity and interfacial peel resistance of the concrete bending member.
Claims
1. A synergistic embedding reinforcement method based on low-carbon geopolymer and small-diameter FRP reinforcement, characterized in that, Includes the following steps: S1. Use a grooving machine to open a groove in the concrete cover at the bottom of the concrete bending member to be reinforced along the direction of force, and wash the concrete debris in the groove with running water. S2. Prepare the geopolymer mortar according to the following mass parts: 500-600 parts slag, 140-150 parts fly ash, 200-300 parts silica fume, 250-300 parts 800-mesh quartz sand, 350-400 parts 70-110-mesh quartz sand, 200-220 parts 40-70-mesh quartz sand, 150-160 parts 20-40-mesh quartz sand, 40-45 parts solid sodium hydroxide, 260-280 parts water, 330-350 parts water glass solution, and 15-25 parts polycarboxylate superplasticizer. First, mix the slag, fly ash, and silica fume evenly. Then, add the various grades of quartz sand and polycarboxylate superplasticizer and dry mix for 1-2 minutes. Finally, add the alkali activator prepared 2 hours prior and wet mix for 3 minutes. The alkaline activator is prepared by first slowly adding water to a water glass solution and stirring, and then adding solid sodium hydroxide until it is completely dissolved. S3. Prepare small-diameter FRP reinforcement bars with a diameter of 0.5-1.5 mm according to the required length of the structure to be reinforced, and clean the dust from the surface of the reinforcement bars; S4. Use alcohol-soaked cotton balls to clean the residue and dust in the tank. After the alcohol has completely evaporated, wet the inner wall of the tank with a wet cotton ball. First, pour the bottom layer of polymer mortar into the tank. Then, evenly arrange the small-diameter FRP reinforcement in the tank. Next, pour the top layer of polymer mortar and vibrate for 4-5 minutes to make the polymer mortar cover each small-diameter FRP reinforcement. Finally, smooth the surface of the polymer mortar. S5. After covering the surface of the reinforcement system with water-retaining cotton and curing it with water for 28 days, the reinforced surface is polished and repaired.
2. The collaborative embedded reinforcement method according to claim 1, characterized in that, The grooving speed in step S1 is controlled at 20-30 cm / min, the grooving width is 10-20 mm, and the grooving depth is determined based on the thickness of the steel reinforcement protective layer of the reinforced concrete bending member.
3. The collaborative embedded reinforcement method according to claim 1, characterized in that, The density of the small-diameter FRP reinforcement is 1.5 g / cm³. 3 The tensile strength is not less than 2000 MPa, the elastic modulus is not less than 210 GPa, and the elongation is not less than 1.8%.
4. The collaborative embedded reinforcement method according to claim 1, characterized in that, In step S3, the small-diameter FRP reinforcement is subjected to surface sandblasting or grinding treatment.
5. The collaborative embedded reinforcement method according to claim 1, characterized in that, The small-diameter FRP reinforcement is a small-diameter CFRP reinforcement.
6. The collaborative embedded reinforcement method according to claim 1, characterized in that, The concrete flexural member to be reinforced is a reinforced concrete beam, and the bottom of the reinforced concrete beam has at least two slots for arranging the small-diameter FRP reinforcement.
